Analysis of Indonesian Human Rights and Islamic Criminal Law on Chemical Castration as An Effort to Tackle Criminal Acts of Sexual Violence Against Children - Ziya’ul Fikri; Joko Setiyono (Eduvest - Journal of Universal Studies, 2024)
This research is motivated by cases of sexual violence in children have a serious impact on children, both directly and long-term. One form of legal protection for children to overcome sexual violence against children, the Government issued Perppu No. 1 of 2016 which was passed into UU No. 17 of 2016. This study aims to find out how the view of human rights in Indonesia and Islamic criminal law regarding chemical castration as an effort to overcome sexual violence in children. This research uses library research method using descriptive analysis approach. The result of this study is in human rights The implementation of chemical castration is an act of violence and is considered contrary to the 1945 Constitution, namely in Article 28 G paragraph 2 and Article 33 paragraph 1 of UU No. 39 of 1999 concerning Human Rights. Meanwhile, Islamic criminal law basically does not recognize castration. The punishment of chemical castration is ta'zir. This study concludes that from the perpetrator's side, this criminal conviction is clearly not in accordance with human rights. From the side of the child as a victim, of course, this chemical castration crime can be an appropriate crime. In Islamic penal law, chemical castration can be imposed if rape committed by the perpetrator is included in an act close to adultery.